MEMBACA KISAH NABI DAUD MENGGUNAKAN SEMIOTIKA ROLAND BARTHES - Santoso, Jarot Nanang; Abror, Indal (UIN Sunan Kalijaga Yogyakarta, 2019)
Roland Barthesâ€™s semiotics, as a science that is concerned in coding, was applied in analyzing the story of the Prophet David. Application of multilevel readings; Heuristic readings and retroactive readings in the story of the Prophet David consisting of 25 lexia texts of the Koran, were found to be of significance identified from certain codes, including: a) hermeunetic code / puzzle code, b) symbolic code â€œDavidâ€ symbol from the ideal leader, c) the semic code or the â€œarkâ€ connotative code means the importance of preserving and preserving relics, d)Â Â the proaretic code / action code â€œDavid fellâ€ means humility acknowledging mistakes not looking at someoneâ€™s status, e) gnomic code or code Cultural â€œGoliath and its troopsâ€ means that there will always be those who spread damage, and during this time Godâ€™s intervention will also contribute to protecting the universe through the other party who spread goodness, and so on.